Clinicopathological and immunohistochemical analysis of Sarcomatoid carcinoma of head and neck mucosal region: a retrospective analysis - Qayoom, Sumaira; Akhtar, Naseem; Kumar, Madhu; Agarwal, Preeti; Maurya, Malti Kumari; Raghuvanshi, Shivanjali; Agarwal, Apoorva; Goel, Madhu Mati (International Journal of Research in Medical Sciences, 2019)
Background: Sarcomatoid carcinoma is a biphasic tumour comprising both of malignant epithelial and mesenchymal elements derived monoclonally from same stem cells. These are unusual variants of squamous cell carcinoma and constitute less than 1% of the head and neck mucosal tumors. Only few studies have been published and needs more understanding to establish treatment guidelines. The aim of this study was to review the cases of carcinosarcoma arising from mucosal sites of head and neck and study their clinical, histological and Immunohistochemical features. Methods: Retrospective data and slides of histologically proven sarcomatoid carcinoma over a period of thirty -four months between January 2016 - October 2018 were retrieved and evaluated for various clinical and histopathological parameters. Results: Total of 22 cases were included in the study and the mean age of presentation was 58years with male: female ration 2:1. Most of the patients (81.8%) presented with a mass lesion of less than 6 months duration. The most common site was oral cavity (68.1%) followed by larynx (22.7%). Clinical stage was known in eleven cases. One case presented with pulmonary metastasis. Histopathologically, epithelial differentiation was identified in nine cases (41%) on morphology and in thirteen cases could be highlighted by cytokeratin positivity. The Mesenchymal component was arranged in sheets (63.7%) and fascicles (31.8%). Marked anaplasia and brisk mitosis wereseen in 54.5% and 19.3% respectively. On immunohistochemistry all 22 cases were positive for Vimentin, twenty cases were positive for cytokeratin/EMA and aberrant mesenchymal markers were expressed in 10% of cases. Follow up was available in eighteen cases out of which fourteen cases died within one year of diagnosis. Conclusions: Diagnosis of sarcomatoid carcinoma is challenging especially on small biopsy because of overlapping features with other spindle cell tumors. Understanding the clinicopathological features facilitates their diagnosis and effective clinical management.